Probabilistic investigation of global mean sea level during MIS 5a based on observations from Cave Hill, Barbados. (1st November 2022) - Tawil-Morsink, Kai; Austermann, Jacqueline; Dyer, Blake; Dumitru, Oana A.; Precht, William F.; Cashman, Miranda; Goldstein, Steven L.; Raymo, Maureen E.
Abstract: Global mean sea level (GMSL) reconstructions from past interglacial periods help us understand the sensitivity of ice sheets to a warming climate. In this study, we focus on Marine Isotope Stage 5a (MIS 5a), a warm period that peaked 82, 000 years ago and for which current GMSL estimates remain widely uncertain (ranging from −28 m to +1 m). Here we reconstruct relative sea level (RSL) based on an extensive and exquisitely preserved fossil coral reef at Cave Hill, Barbados, which has not been examined before. We dated one coral sample ( Acropora palmata ) from this outcrop using U-series dating and obtained a closed system age of 82.5 ± 0.4 ka and an open system age of 83.3 ± 0.7 ka (2 σ ), which confirm that the reef formed during MIS 5a. We determine RSL based on the elevation of 222 fossil corals within the outcrop from three species ( Acropora palmata, Siderastrea radians, Favia fragum ). The coral elevations are combined using Bayesian inference to obtain a posterior common RSL, with present-day water depths of each species as priors. We use our inference scheme and synthetic datasets to explore the number and species of corals needed for a robust RSL estimate and find that if approximately 5 corals are sampled, roughly half of which have a narrow living depth range (0 to ∼10 m), the accuracy and precision of the inferred RSL is around 1.5 m. This value improves to less than 0.5 m if more corals (approximately 20) are sampled, especially if these have narrow living depth ranges. These tests can guide future coral sampling at other outcrops. After inferring RSL from the real coral elevations, we correct it for long-term uplift, using the elevation of the adjacent MIS 5e sea level outcrop to calculate an uplift rate of 0.522 ± 0.036 m/kyr (1 σ ), and for glacial isostatic adjustment. We find that GMSL most likely peaked at −22.3 m relative to present GMSL (−32.5 m to −10.7 m, 95% credible interval). This work provides a new estimate for MIS 5a GMSL that is lower than results from most previous studies, and confirms sequentially decreasing GMSL during the MIS 5e, 5c, and 5a precessional insolation peaks, indicating increased ice sheet growth and cooling into the ice age following the peak interglacial MIS 5e. Highlights: We reconstruct global mean sea level (GMSL) for MIS 5a using a fossil coral reef at Cave Hill, Barbados. We dated one coral ( Acropora palmata ) from this outcrop to confirm its MIS 5a age. We use Bayesian inference to determine relative sea level (RSL) based on 222 fossil coral elevations. MIS 5a GMSL was most likely −22.3 m relative to present (−32.5 m to −10.7 m, 95% credible interval). Our MIS 5a GMSL is consistent with decreasing GMSL over the MIS 5e, 5c, and 5a insolation peaks.